Seismic response of self centring hysteretic SDOF systems. - Christopoulos, Constantin (Earthquake engineering & structural dynamics.)
The seismic response of single degree of freedom (SDOF) systems incorporating flag shaped hysteretic structural behaviour, with self centring capability, is investigated numerically. For a SDOF system with a given initial period and strength level, the flag shaped hysteretic behaviour is fully defined by a post yielding stiffness parameter and an energy dissipation parameter. A comprehensive parametric study was conducted to determine the influence of these parameters on SDOF structural response, in terms of displacement ductility, absolute acceleration and absorbed energy. This parametric study was conducted using an ensemble of 20 historical earthquake records corresponding to ordinary ground motions having a probability of exceedance of 10 percent in 50 years, in California. The responses of the flag shaped hysteretic SDOF systems are compared against the responses of similar bilinear elasto plastic hysteretic SDOF systems. In this study the elasto plastic hysteretic SDOF systems are assigned parameters representative of steel moment resisting frames (MRFs) with post Northridge welded beam to column connections. In turn, the flag shaped hysteretic SDOF systems are representative of steel MRFs with newly proposed post-tensioned energy dissipating connections. Building structures with initial periods ranging from 0.1 to 2.0s and having various strength levels are considered. It is shown that a flag shaped hysteretic SDOF system of equal or lesser strength can always be found to match or better the response of an elastoplastic hysteretic SDOF system in terms of displacement ductility and without incurring any residual drift from the seismic event.